PENGEMBANGAN KEPEMIMPINAN INKLUSIF DALAM PENDIDIKAN ISLAM DI ERA 5.0: MENINGKATKAN KOLABORASI DIGITAL ANTARA SEKOLAH, PESANTREN, DAN MASYARAKAT - Budiman, Septian Arief; Nuruddin, Muhammad Mamduh; Hidayatulloh, Riyan (STKIP Pesisir Selatan, 2025)
This study aims to examine the development of inclusive leadership in Islamic educational institutions in the 5.0 Era, with a focus on efforts to increase digital collaboration between schools, Islamic boarding schools, and the community. The background of this study is the urgent need to respond to the challenges of the era marked by digital transformation and increasing demands for public participation in the world of education. This study uses a qualitative-descriptive approach through library research, by analyzing literature related to inclusive leadership, Islamic education, and the development of digital technology in the context of education. The results of the study indicate that inclusive leadership supported by the use of digital technology can strengthen synergy between Islamic educational institutions and increase the active role of the community in decision-making and implementation of educational programs. This type of leadership also encourages openness of information, cross-sectoral participation, and improving the quality of educational services based on Islamic values. The novelty of this study lies in the combination of the concept of inclusive leadership with a digital-based collaborative approach in Islamic educational institutions, which has not previously been widely discussed in an integrative manner in Islamic educational leadership studies.